2014
DOI: 10.3390/ijms151120607
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms Underlying the Effects of Statins in the Central Nervous System

Abstract: 3-Hydroxy-3-methylglutaryl coenzyme A reductase inhibitors, commonly referred to as statins, are widely used in the treatment of dyslipidaemia, in addition to providing primary and secondary prevention against cardiovascular disease and stroke. Statins’ effects on the central nervous system (CNS), particularly on cognition and neurological disorders such as stroke and multiple sclerosis, have received increasing attention in recent years, both within the scientific community and in the media. Current understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
129
0
10

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(148 citation statements)
references
References 168 publications
3
129
0
10
Order By: Relevance
“…This cell cycle arrest was accompanied by intrinsic apoptosis as demonstrated by diminished B-cell lymphoma 2 (Bcl-2) protein levels, increased cytosolic cytochrome c and active caspase 9 and caspase 3 levels. In human glioblastoma cells, previous studies have revealed that erivastatin, pitavastatin and fluvastatin are potent anti-proliferative agents (10,11). In addition, one clinical trial revealed that fluvastatin reduced tumour proliferation and increased apoptotic activity in high-grade, stage 0/1 breast cancer (12).…”
Section: Introductionmentioning
confidence: 99%
“…This cell cycle arrest was accompanied by intrinsic apoptosis as demonstrated by diminished B-cell lymphoma 2 (Bcl-2) protein levels, increased cytosolic cytochrome c and active caspase 9 and caspase 3 levels. In human glioblastoma cells, previous studies have revealed that erivastatin, pitavastatin and fluvastatin are potent anti-proliferative agents (10,11). In addition, one clinical trial revealed that fluvastatin reduced tumour proliferation and increased apoptotic activity in high-grade, stage 0/1 breast cancer (12).…”
Section: Introductionmentioning
confidence: 99%
“…Zahamowanie wątrobowej syntezy cholesterolu zwiększa obwodowy klirens tego steroidu, co zmniejsza stężenie frakcji LDL, do czego przyczynia się również zahamowanie wątrobowej produkcji apolipoproteiny B100, wchodzącej w skład LDL. Statyny zwiększają także stężenie frakcji HDL oraz wykazują inne korzystne efekty sercowo-naczyniowe, niezależne od ich wpływu na parametry lipidowe, jak poprawa integralności śródbłonka naczyniowego, zmniejszanie i kontrolowanie reakcji zapalnej w świetle naczynia, hamowanie proliferacji mię-śniówki gładkiej i procesu remodelingu naczyniowego [57,58]. Wzrastająca liczba doniesień sugeruje, iż część z tych efektów (zmniejszenie produkcji apoB100, wzrost HDL) jest mediowana przez agonistyczny wpływ statyn na PPAR-α, co ponadto wyjaśnia obserwowany, analogiczny do fi bratów, wpływ wybranych związków z tej klasy (simwastatyna, prawastatyna, ceriwastatyna) na obniżanie stężenia trójglicerydów [59,60].…”
Section: Wpływ Na Ppar Jako Dodatkowy Aspekt Farmakodynamiki Sartanówunclassified
“…Within liver cells, ATV disrupts cholesterol biosynthesis by blocking 3-hydroxy-3-methylglutaryl-coenzyme A reductase, which reduces the amount of cholesterol released into the blood. As a consequence, low-density lipoprotein cholesterol uptake by liver cells increases and blood cholesterol levels diminish (6). However, in clinical trials of ATV, pharmacokinetic parameters including maximum plasma concentration (C max ), time to reach C max (T max ), area under the plasma concentration-time curve (AUC) from time 0 to the time of last measurement (AUC 0-t ), AUC from time 0 extrapolated to infinity (AUC 0-∞ ), apparent clearance of the fraction dose absorbed (Cl/F), elimination rate constant in the terminal drug phase (Ke) and the half-life in the terminal drug phase (T 1/2 ) are variable (7).…”
Section: Introductionmentioning
confidence: 99%